Food safety in the horticultural sector in Ghana: challenges, risk factors and interventions - Essilfie, Gloria Ladjeh; Lamptey, Samuel; Baddoo, Rosalyne Naa Norkor; Amenorpe, Godwin; Hevi, Walter; Owusu, Margaret; Atupra, Faustina (Frontiers in Sustainable Food Systems, 2023)
The fruit and vegetable industry remains one of Ghana’s most promising agricultural sectors mainly because of heightened awareness of the health benefits associated with their consumption. However, food safety is of ultimate concern due to the association of foodborne hazards resulting in escalation of foodborne illness. This report is a review of key foodborne hazards in Ghana’s horticultural value chain. The study identified the risk factors and hazards that contaminate fruits and vegetables in addition to existing methods for mitigating health risks and reducing pathogen levels in the produce. The study revealed that enteric pathogens such as Escherichia coli and Salmonella spp. mainly contaminate produce through fresh manure and contaminated irrigation water used during the production of vegetables. Chemical hazards identified included pesticides (organochlorine pesticides) and heavy metals such as cadmium, arsenic, chromium, and lead. Physical hazards identified included twigs, roots, sand, and stones. Washing fruits and vegetables thoroughly with potable water and sanitizing with vinegar and Chlorine solutions were among the common practices stakeholders adopted to reduce microbial levels. Soil remediation was also reported as a common approach for reducing chemical contaminants in agricultural fields. The study, therefore, recommends establishing a traceability system as well as appropriate measures and standards for hygienic practices for fresh fruits and vegetables produced and sold on the local market in Ghana. Value chain actors should be sensitized regularly on measures and interventions that can be employed to significantly reduce the levels of foodborne hazards and associated risks.